Individual versus collaborative computer-supported concept mapping : a study with adult learners - Coutinho, Clara Pereira (2009)
In this paper we report how two groups of in-service teachers used concept mapping for studying the curricular subject Research Methods in Education as part of a post graduate teacher education program during the 1st semester of 2008-2009. Teachers build electronic concept maps as a constructivist learning strategy to organize and reflect on the course readings, to plan assessment projects and to compare and contrast information of classroom discussions. Concept maps were built using CmapTools software individually (group A) and in teams (group B) on the same topics of the RME program. Concept maps were analysed considering five dimensions reported in literature: total nº of concepts, nº of valid links, hierarchical levels, cross links, examples and map visual format (vertical/horizontal/radial). Results show that individual maps are more diversified in terms of visual representations; that collaborative maps score higher in all five dimensions considered in the analysis; and that statistical differences are found when applying the Novak and Gowin (1984) formula to the concept maps due to the presence of more cross-links presented on group maps when compared to individual ones.